2002
DOI: 10.1200/jco.2002.04.016
|View full text |Cite
|
Sign up to set email alerts
|

HER2 in Brain Metastases: Issues of Concordance, Survival, and Treatment

Abstract: To the Editor: We read with interest the article by Seidman et al 1 describing the risks of adverse cardiac events associated with trastuzumab therapy for metastatic breast cancer, published in the March 1, 2002, issue of the Journal of Clinical Oncology. In that retrospective review of records from 1,219 patients enrolled onto one of seven phase II or III clinical trials, the risk of adverse cardiac events was low (3% to 7%) when trastuzumab was prescribed alone. In contrast, the risk was higher when trastuzu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 8 publications
2
28
1
Order By: Relevance
“…Additionally, in that study the incidence of bone relapse in patients administered trastuzumab was significantly lower compared to those who did not receive this compound (15 and 91%, respectively). However, other studies did not demonstrate survival benefit of trastuzumab in patients with brain relapse [16,40]. The median survival in this series was 3.2 years and the median survival from the diagnosis of brain relapse-9 months.…”
Section: Discussioncontrasting
confidence: 67%
“…Additionally, in that study the incidence of bone relapse in patients administered trastuzumab was significantly lower compared to those who did not receive this compound (15 and 91%, respectively). However, other studies did not demonstrate survival benefit of trastuzumab in patients with brain relapse [16,40]. The median survival in this series was 3.2 years and the median survival from the diagnosis of brain relapse-9 months.…”
Section: Discussioncontrasting
confidence: 67%
“…Negative-positive alterations were observed in 15.1% of ER-negative, 7.5% of PR-negative and 11.8% of HER2-negative primary tumors in our study. The HER2 status was highly maintained and the concordance rate between primary tumors and systemic metastases was shown to be 97% by a previous study (41). We demonstrated that 89% of HER2-positive patients treated with trastuzumab prior to the development of brain metastases maintained a positive status in brain metastases.…”
Section: Discussionmentioning
confidence: 57%
“…In previous reports, the discordance rates of 0% to 26% in HER-2 overexpression and amplification was found between primary breast tumors and the matching distant metastases (41 -43). In metastatic brain tumors, the concordance reached 97% in HER-2 overexpression compared with primary breast cancers (44). The expression of EGFR showed primary tumor/metastasis discordance of 33.3% in NSCLC by immunohistochemistry analysis (45).…”
Section: Discussionmentioning
confidence: 99%